KONTROL DIRI DAN IMPULSIVE BUYING PRODUK FASHION PADA MAHASISWA PSIKOLOGI UNIVERSITAS KRISTEN SATYA WACANA PENGGUNA E-COMMERCE SHOPEE - Lydia Alamanda; Christiana Hari Soetjiningsih (ADISAM PUBLISHER, 2023)
Along with the development of e-commerce that facilitates the shopping process, people are increasingly shopping impulsively without any careful thought. The younger generation who pay great attention to appearance often make purchases of fashion products through e- commerce. Unknowingly, they make purchases without adequate planning and consideration. This study aims to determine the relationship between self-kontrol and impulsive buying behavior in Psychology students at Satya Wacana Christian University when shopping for fashion at Shopee. Data collection was carried out using a questionnaire. Participants in this study amounted to 103 participants with purposive sampling method. The results showed a correlation coefficient (r) of 0,762 with a significance value of = 0,000 (p <0.05), which means that there is a significant negative relationship between impulse buying and self-kontrol. This shows that the greater the self-kontrol, the lower the tendency for impulse buying. Conversely, if self-kontrol is low, then the tendency for impulsive buying is higher